Kinematic Analysis and Dynamic Optimization Simulation of a Novel Unpowered Exoskeleton with Parallel Topology. (9th July 2019) - Yan, Qiang; Zhang, Jianjun; Li, Bin; Zhou, Liang
Abstract : This paper studies the kinematic and dynamic analysis of a novel unpowered exoskeleton with topology. Firstly, the kinematics of the unpowered exoskeleton is analyzed by the derivation of the closed-loop position equation, and the forward position problems of the exoskeleton are obtained. Secondly, with the aim of doing some research in the dynamics, two of links for the exoskeleton are changed into flexible links. Some shapes concerning some parameters are acquired by simulation with fitting curve method. Thirdly, meanwhile, the dynamic model is built by using Lagrange method. Fourthly, the gait experiment is acquired with the aim of obtaining the law of the human joints. Fifthly, the dynamic model is verified by Adams software and the theoretical calculation. Meanwhile, an optimization is completed in the Adams software. The most reasonable spring stiffness is acquired. Finally, some conclusions are enumerated to show the properties of the mechanisms.